Case Report: Congenital candidemia due to non-albicans Candida species–A report of two cases and literature review - Yu, Xiaojing; Zhang, Lan; Wen, Lijun; Zhong, Yuli; Li, Minxu (Frontiers in Medicine, 2025)
Congenital candidiasis caused by non-albicans Candida (NAC) species represents a life-threatening condition with significant underreporting in clinical literature. It mainly manifests as systemic invasive candidiasis. Premature infants are affected more easily due to the immaturity of their immune system. Risk factors such as those with in vitro fertilization (IVF)-associated, premature membrane rupture, and the presence of intrauterine devices are reported to be associated with congenital systemic candidiasis (CSC). We present two cases of extremely preterm neonates diagnosed with congenital systemic candidiasis (CSC): case 1 involved Candida tropicalis infection, while case 2 exhibited Candida glabrata infection. Based on the literature reports, we conduct a review on CSC due to NAC. We highlight the importance of early recognition and treatment in neonates born to mothers with risk factors. It is recommended that maternal screening for candidiasis and prophylactic antifungal treatment should be conducted promptly for mothers with risk factors when signs of preterm birth appear. CSC should be taken into consideration when unaccountable disseminated infections occur in preterm infants and antifungal therapy should be administered as soon as possible.